Petrographic, Mineralogical and Geo-mechanical Characteristics of Marble from Mohmand District, Pakistan: Implications for its Use in Construction Industry - Anjum, Naveed; Hidayat, Hamza; Ali, Nowrad; Iqbal, Usman; Yazdi, Abdollah (International Journal of Economic and Environmental Geology, 2024)
This study aims to evaluate the suitability of marble deposits from Mohmand district for use in the construction industry. By employing an integrated approach that combines petrographic analysis, chemical assessments, and physico-mechanical testing, the study seeks to provide a comprehensive understanding of the marble's properties. Although, megascopically indistinguishable, the petrographic analysis identifies two varieties of carbonate rocks: Calcitic-marble and dolomitic-marble. The marble from the Sapari quarry is petrographically fine to medium grained and dominantly composed of subhedral to anhedral calcite (84-86%), dolomite (8-10%), quartz (6-8%) and trace amount of micrite and hence classified as calcitic-marble. Owing to less contents of dolomite and unstrained quartz, the calcitic-marble reveals very low reactive quartz and magnesium in the rock, hence no expansion if used in concrete with ordinary Portland cement (OPC). The petrographic and chemical investigations, therefore, endorse their innocuous non-reactive character for both alkali silica reactivity (ASR) and alkali carbonate reactivity (ACR). In contrast, the marble from Qaroon Ghundai quarry is mineralogically dolomitic and texturally fine grained, where subhedral to anhedral dolomite constitutes the major phase (97˗98 %), while quartz and micrite occur as the minor phases. The results of the cube test of the dolomitic-marble demonstrate an expansion by 0.28 % which lies above threshold limit of 0.10% thus endorse the potential to initiate ACR. Hence, this marble is declared deleterious with respect to ACR. With the exception of soundness value, the dolomitic-marble produces relatively higher values for UCS, specific gravity, bulk density, LA and Schmidt hammer as compared to the calcitic-marble. The comparative analysis shows that the calcitic-marble is suitable for high alkali cement-concrete and asphalt-works as a coarse aggregate. Alternatively, the dolomitic-marble is only declared suitable for asphalt-based concrete due to its ACR potential, which endorses the significance of mineralogy and textures in controlling the physical and mechanical properties of rocks. Keywords: Petrography, calcitic-marble, dolomitic-marble, construction industry, alkali carbonate reactivity.